Comparison of DNAzyme activity for the development of an immobilized heme sensor. (5th January 2018) - Hughes, Natalie; Nguyen, Nancy; Daley, Deanna-Kaye; Grennell, Justin; Gee, Amira; Ali, Mehnaaz F.
ABSTRACT: Point-of-care systems require highly sensitive, quantitative and selective detection platforms for the real-time multiplexed monitoring of target analytes. To ensure facile development of a sensor, it is preferable for the detection assay to have minimal chemical complexity, contain no wash steps and provide a wide and easily adaptable detection range for multiple targets. Current studies involve label-free detection strategy for relevant clinical molecules such as heme using G-quadruplex based self-assembly. We have explored the measurement of binding and kinetic parameters of various G-quadruplex/heme complexes which are able to self-associate to form a DNAzyme with peroxidase mimicking capabilities and are critical to nucleic acid research. The detection strategy includes immobilizing the G-quadruplex sequences within a polymer matrix to provide a self-assembly based detection approach for heme that could be translated towards other clinically relevant targets.